Climate change and the oil industry: Common problem, different strategies - Skjaerseth, Jon; Skodvin, Tora (Manchester University Press, 2003)
Multinational corporations are not merely the problem in environmental concerns, but could also be part of the solution. The oil industry and climate change provide the clearest example of how the two are linked; what is less well-known is how the industry is responding to these concerns. This volume presents a detailed study of the climate strategies of ExxonMobil, Shell and Statoil. With an innovative analytical approach, the authors explain variations at three decision-making levels: within the companies themselves, in the national home-bases of the companies, and at an international level. The analysis generates policy-relevant knowledge about whether and how corporate resistance to a viable climate policy can be overcome. The analytical approach developed by the authors is also applicable to other areas of environmental degradation where multinational corporations play a central role. The book is invaluable to students, researchers and practitioners interested in national and international environmental politics and business environmental management.